Editors' Introduction: Miscommunication. (10th May 2018) - Healey, Patrick G. T.; de Ruiter, Jan P.; Mills, Gregory J.
Abstract: Miscommunication is a neglected issue in the cognitive sciences, where it has often been discounted as noise in the system. This special issue argues for the opposite view: Miscommunication is a highly structured and ubiquitous feature of human interaction that systematically underpins people's ability to create and maintain shared languages. Contributions from conversation analysis, computational linguistics, experimental psychology, and formal semantics provide evidence for these claims. They highlight the multi‐modal, multi‐person character of miscommunication. They demonstrate the incremental, contingent, and locally adaptive nature of the processes people use to detect and deal with miscommunication. They show how these processes can drive language change. In doing so, these contributions introduce an alternative perspective on what successful communication is, new methods for studying it, and application areas where these ideas have a particular impact. We conclude that miscommunication is not noise but essential to the productive flexibility of human communication, especially our ability to respond constructively to new people and new situations. Abstract : Healey et al. introduce the special issue with a brief overview of work on communication in the Cognitive Sciences and some of the historical and conceptual influences that have marginalized the study of miscommunication. Drawing on more recent work in Cognitive Science and Conversation Analysis they argue that miscommunication is in fact a highly structured, ubiquitous phenomenon that is fundamental to human interaction.